Consumer Perception of product quality in quick commerce: a comparative study of Zepto and Blinkit (Journal of Informatics Education and Research, 2025)
Quick commerce (Q-commerce) has revolutionized e-commerce by providing ultra-fast deliveries within 10 to 30 minutes. While speed drives its popularity, product quality plays a crucial role in consumer trust and satisfaction. This study analyzes consumer perceptions of product quality in Q-commerce by comparing Zepto and Blinkit, two major players in India. It examines key factors such as freshness, packaging, and delivery efficiency using data collected from 117 respondents in Mumbai. Quantitative analysis, including regression and t-tests, reveals that product quality significantly influences consumer perception, with freshness being the most critical factor. The findings show that Blinkit (M = 3.82) is rated higher than Zepto (M = 3.46), indicating a statistically significant difference. The study underscores the need for Q-commerce platforms to prioritize quality alongside speed to enhance customer satisfaction. Future research could explore factors like pricing, brand reputation, and customer service to offer deeper insights into consumer preferences.